2023
DOI: 10.3390/chemengineering7050092
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Thermal Annealing and Changing the Concentration of GO in GO/PVA Nanocomposites on Their Structural, Electrical, and Optical Properties

Lala Gahramanli,
Mustafa Muradov,
Goncha Eyvazova
et al.

Abstract: The present research involves producing graphene oxide (GO) using the Hummers method, generating a composite using GO and PVA, and analyzing these composites’ structural and optical characteristics. PVA and GO were used in varied percentages to deal with the issue of how the features of GO/PVA alter depending on concentration. The impact of thermal annealing on the structure and optical characteristics of GO/PVA materials at various concentrations were also investigated. UV-VIS was used to investigate the band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…1 Studies conducted on PVA-GO nanocomposites have revealed an intriguing trend: as the concentration of GO within the nanocomposite increases, the band gap value decreases. 8,9 The band gap is an important parameter that determines the electrical behavior and optical properties of materials. The decrease in the band gap suggests that the incorporation of GO alters the electronic structure of the nanocomposite, leading to changes in its optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies conducted on PVA-GO nanocomposites have revealed an intriguing trend: as the concentration of GO within the nanocomposite increases, the band gap value decreases. 8,9 The band gap is an important parameter that determines the electrical behavior and optical properties of materials. The decrease in the band gap suggests that the incorporation of GO alters the electronic structure of the nanocomposite, leading to changes in its optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%